Are Students at the School Acceleration Program are More Likely to Experience Anxiety Disorders? - Dhita Adriany (HM Publisher, 2021)
Introduction: The Acceleration Program and the International Standard School Pilot Project (RSBI) are currently being held in Indonesia. Previous research stated that the anxiety of students with acceleration was higher than that of non-accelerated students (regular). Currently, the regular program has mainly been replaced by the RSBI program. This research was conducted to determine differences in the level of anxiety of students who take the accelerated program and the RSBI program. Methods: The study was conducted using a cross-sectional method, and the sampling was determined by purposive sampling. This study took the population of students of Junior High School 1 Purwokerto. Primary data were collected in the form of friendship quality questionnaires, Rahe-Holmes Social Readjustment Rating Scale life events questionnaire, body image questionnaire (Body Shape Questionnaire) and TMAS anxiety questionnaire (Taylor Manifest Anxiety Scale). Results: Accelerated students who experienced anxiety above the average were 8 (40%) students and 12 (60%) students experienced anxiety below average. Non-accelerated students (RSBI) who experienced anxiety above the average were 15 (75%) students and 5 (25%) students experienced anxiety below average. Conclusion: There is a significant difference in the level of anxiety of students who take the acceleration program and RSBI, where the anxiety of RSBI students is more than that of accelerated students.